Concrete in extreme environments - Bull, John W.; Zhou, Xiangming (Professor in civil engineering) (Whittles Publishing, 2018)
This provides indicative case studies of concrete in extreme environments or conditions and gives vital insights to help designers and users of concrete in unusual situations. A truly international authorship.
Keywords: Concrete construction.; Extreme environments.; elektronické knihy; electronic books